Don't Blink : A Novel - Patterson, James 1947; Roughan, Howard (New York : Little, Brown, 2010)
After he witnesses a hit on a mob lawyer that sparks an all-out mafia war, reporter Nick Daniels captures a key piece of evidence and launches a relentless investigation, during which he endures humiliation, threats, and violence.
Keywords: Journalists -- Fiction; Gangs -- Fiction; Large print books; New York (N.Y.) -- Fiction; Law stories; Fiction